Recent Progress in Space Physiology and Aging - Strollo, Felice; Gentile, Sandro; Strollo, Giovanna; Mambro, Andrea; Vernikos, Joan (Frontiers in Physiology, 2018)
Astronauts coming back from long-term space missions present with different health problems potentially affecting mission performance, involving all functional systems and organs and closely resembling those found in the elderly. This review points out the most recent advances in the literature in areas of expertise in which specific research groups were particularly creative, and as they relate to ageing and to possible benefits on Earth for disabled people. The update of new findings and approaches in space research refers especially to neuro-immuno-endocrine-metabolic interactions, optic nerve edema, motion sickness and muscle-tendon-bone interplay and aims at providing the curious - and even possibly naïve young researchers – with a source of inspiration and of creative ideas for translational research.